1987
DOI: 10.1128/jvi.61.10.2956-2961.1987
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic analysis of equine infectious anemia virus (EIAV) variants by using monoclonal antibodies: epitopes of glycoprotein gp90 of EIAV stimulate neutralizing antibodies

Abstract: Monoclonal antibodies produced against the prototype cell-adapted Wyoming strain of equine infectious anemia virus (EIAV), a lentivirus, were studied for reactivity with the homologous prototype and 16 heterologous isolates. Eighteen hybridomas producing monoclonal antibodies (MAbs) were isolated. Western blot (immunoblot) analyses indicated that 10 were specific for the major envelope glycoprotein (gp9O) and 8 for the transmembrane glycoprotein (gp45). Four MAbs specific to epitopes of gp9O neutralized protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…In contrast, no variation is observed in the viral core proteins (Salinovich et al, 1986). Comparisons of peptide and genomic maps of virus isolates recovered from sequential febrile episodes reveal each isolate to be structurally unique, with variation occurring in a random, non-cumulative process (Payne et al, 1987b;Hussain et al, 1987). Rapid epitope alterations in gp90 and gp45 have been documented using neutralizing monoclonal antibodies against the virion surface glycoproteins (Hussain et al, 1987).…”
Section: Antigenic Variation In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, no variation is observed in the viral core proteins (Salinovich et al, 1986). Comparisons of peptide and genomic maps of virus isolates recovered from sequential febrile episodes reveal each isolate to be structurally unique, with variation occurring in a random, non-cumulative process (Payne et al, 1987b;Hussain et al, 1987). Rapid epitope alterations in gp90 and gp45 have been documented using neutralizing monoclonal antibodies against the virion surface glycoproteins (Hussain et al, 1987).…”
Section: Antigenic Variation In Vivomentioning
confidence: 99%
“…Comparisons of peptide and genomic maps of virus isolates recovered from sequential febrile episodes reveal each isolate to be structurally unique, with variation occurring in a random, non-cumulative process (Payne et al, 1987b;Hussain et al, 1987). Rapid epitope alterations in gp90 and gp45 have been documented using neutralizing monoclonal antibodies against the virion surface glycoproteins (Hussain et al, 1987). Selective immune pressure has been hypothesized as the driving force behind the antigenic variation seen in clinical cases of EIA Salinovich et al, 1986;Kono et al, 1973a,b).…”
Section: Antigenic Variation In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that serum from an EIAVinfected animal can neutralize virus isolates recovered from prior but not subsequent disease episodes and that each disease episode is associated with a novel predominant antigenic variant (16,25). Biochemical (25,33,36,38) and immunological (14,32) studies of the predominant virus isolate recovered during disease episodes indicate that the two glycoproteins, gp90 (SU protein) and gp45 (TM protein), vary extensively. In addition, the predominant viruses isolated from sequential febrile episodes in a single pony were shown to be different at the genetic level by RNase mapping experiments (29,33) and by sequence analysis of the envelope (env) gene (30).…”
mentioning
confidence: 99%
“…Sequence analysis showed that much of the genetic variation in gp90 was clustered in a single area termed the variable region (30). Ball et al (3) localized a principal neutralizing domain (PND) to the gp90 variable region, which accounts for the variable reactivity of different virus isolates to PND-specific, neutralizing monoclonal antibodies (14). Additional studies on EIAV sequence diversity have yielded similar results and have identi-fied a second highly variable segment of the genome within the U3 region of the long terminal repeat (LTR) (1,6,30,31,34).…”
mentioning
confidence: 99%